Oral squamous cell carcinoma adjacent to dental implant: a case report with a long-term follow-up - Leandro Ribeiro, Marco Túlio; Ramoa Pires, Fabio; de Andrade Elias, Rogerio; de Abreu Alves , Fábio; Santos-Silva , Alan Roger; Agustin Vargas, Pablo; Kowalski, Luiz Paulo; Ajudarte Lopes, Marcio (Journal of Oral Diagnosis, 2024)
Head and neck cancers are a growing global health concern, with oral squamous cell carcinoma (OSCC) accounting for 90-95% of all cases within this region. OSCC near dental implants can resemble benign inflammatory lesions, posing diagnosis challenging. A 74-year-old man presented with an ulcerated, asymptomatic lesion in the upper right alveolar mucosa, initially misdiagnosed as a benign inflammatory condition due to its proximity to a dental implant. Afterwards the lesion was identified as OSCC, and the patient underwent surgical treatment. Three years post-surgery, a white plaque appeared near the grafted area and was diagnosed as oral leukoplakia. Although, over the course of fourteen years, the patient had no recurrences or metastases. Therefore, clinicians should be aware that while most lesions around dental implants are of inflammatory origin, OSCC must be considered in differential diagnosis in cases that do not respond to standard treatments.